Gas-Phase Studies of NMR Shielding and Indirect Spin–Spin Coupling in [sup.13]C-Enriched Ethane and Ethylene - Wilczek, Marcin; Jackowski, Karol (Molecules (Basel, Switzerland), 2024)
[sup.13]C and [sup.1]H NMR spectra were observed as the function of density in 1,2-[sup.13]C-enriched ethane and ethylene for the pure gaseous compounds and their binary mixtures with xenon and carbon dioxide gases as the solvents. All the chemical shifts and indirect spin–spin couplings were linearly dependent on the solvent density. The appropriate NMR parameters (σ and [sup.n]J) in isolated [sup.13]C[sub.2]H[sub.6] and [sup.13]C[sub.2]H[sub.4] molecules and the coefficients responsible for the binary molecular interactions were determined and compared with previous similar measurements and selected calculated shielding data. The newly obtained [sup.13]C shielding values in the isolated ethane and ethylene molecules suggest visible secondary isotope effects due to the additional carbon-13 atom. All the investigated shielding parameters depend on intermolecular interactions, and the dependence of [sup.13]C shielding is much more marked. In contrast, the indirect spin–spin couplings in [sup.13]C[sub.2]H[sub.6] and [sup.13]C[sub.2]H[sub.4] molecules are almost independent of solvent molecules. Their [sup.n]J values determined in liquids over sixty years ago are generally consistent with the same [sup.n]J parameters in isolated [sup.13]C[sub.2]H[sub.6] and [sup.13]C[sub.2]H[sub.4] molecules.